Feeling Colour: Chromatic Embodiment in Film Culture, 1950s–1960s - Lameris, Bregtje (Open Book Publishers, 2025)
The shift back from quasi monochrome to coloured motion picture during the 1950s and 1960s famously provided moviegoers the dazzling opportunity to more fully engage their senses, all the while opening new modes of affective possibilities for filmmakers. Set against the intersection of media studies, emotion theory, biology, and digital humanities, Feeling Colour: Chromatic Embodiment in Film Culture (1950s-1960s) delves into the role colour played in the oft-fraught relationship between cinema and its audiences. This transnational analysis of an extensive range of midcentury cinematography examines the multilayered effects which extend beyond the silver screen, offering a high-level theoretical elaboration and in-depth historical exploration of both experimental and mainstream movies. Lameris takes an interdisciplinary perspective, examining the different ways colour creates—or was believed to create—embodied reactions. From perception theory and 'putting the nerves in motion’, to colour psychology and how to ‘steer’ the spectator, to cross-modal perception (or ‘synaesthesia’), Lameris asks how how colours and feelings in film are entangled in the colour cultures, discourses and beliefs of a particular historical context. With its influential cultural scholarly contribution and accessible writing style, this book will delight both students and specialists in film and media studies. In addition, those interested in the history and use of color in advertising, neuroscience, gender studies, and emotion will find the book engaging and useful.